Pengaruh bauran pemasaran terhadap minat beli kembali pada Sorai Steamboat and Grill Bandung - Hana Nurfadilah; Setia Rudiman; Ramayani Yusuf (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study aims to determine the effect of the 4P marketing mix consisting of price, product, promotion, and place on repurchase intention. The research population of Sorai Steamboat and Grill Bandung products customers, a sample of 50 respondents with snowball sampling technique. Using quantitative research methods, questionnaires were prepared using a Likert scale distributed using a google form, and data analysis techniques using multiple linear regression. The results show that product and price are the main factors in the occurrence of purchase intention and consumers do not pay too much attention to promotions and places in determining repurchase. This happens because Sorai Steamboat and Grill Bandung have produced quality products at competitive prices, but this restaurant has not been optimal in promoting and procuring places. As for promotion and place, it does not affect repurchase, this happens because Sorai Steamboat & Grill has produced quality products at competitive prices, but this restaurant has not been optimal in promoting and procuring places.